2019
DOI: 10.18203/2320-6012.ijrms20195000
|View full text |Cite
|
Sign up to set email alerts
|

Role of cartridge-based nucleic acid amplification test to diagnose tuberculosis at tertiary care teaching hospital in Rajasthan, India

Abstract: Background: Tuberculosis is one of the top 10 causes of death worldwide as per the Global TB report 2017, the estimated incidence of TB in India was approximately 28,00,000 cases accounting for about a quarter of the world’s TB cases (10 million). It is of utmost important to diagnose early and treat it to reduce disease transmission. GeneXpert MTB/RIF, an automated cartridge-based molecular technique detects Mycobacterium Tuberculosis and rifampicin resistance within two hours, has been recommended by WHO for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Male patients made up 74% of those with MTB positivity. Our results are in line with those of recent studies in India that found that 76%, 75%, 70.5%, 71%, and 72% of TB patients were males, as reported [29][30][31][32] . According to the WHO study from 2021, adult males, who made up 56% of all TB cases in 2019, have the highest prevalence of the disease [6].…”
Section: Discussionsupporting
confidence: 93%
“…Male patients made up 74% of those with MTB positivity. Our results are in line with those of recent studies in India that found that 76%, 75%, 70.5%, 71%, and 72% of TB patients were males, as reported [29][30][31][32] . According to the WHO study from 2021, adult males, who made up 56% of all TB cases in 2019, have the highest prevalence of the disease [6].…”
Section: Discussionsupporting
confidence: 93%